A tributação das rendas auferidas por empresas não-residentes no Brasil - Miguel, Eduardo Luís Durante (2007)
The present work has the purpose of analyzing the incidence of the income tax on the activities developed by enterprises that don t reside in Brazil, searching its validity through the confrontation with many juridic concepts, like sovereignty, territoriality, universality, permanent establishment, gains and economic and juridical availability